Culinary treatments impact the digestibility and protein quality of edible insects: a case study with Tenebrio molitor and Gryllus assimilis - Lampová, Barbora; Doskočil, Ivo; Kulma, Martin; Kurečka, Michal; Kouřimská, Lenka (Frontiers in Nutrition, 2024)
The escalating global population is anticipated to intensify the demand for high-quality proteins, necessitating the exploration of alternative protein sources. Edible insects are a promising solution, owing to their nutritional richness and sustainability. However, their digestibility and protein quality, particularly after culinary treatment, remains underexplored. In the present study, we investigated the effects of various culinary treatments on the protein digestibility of two insect species, Tenebrio molitor and Gryllus assimilis. Our findings revealed that culinary treatments such as boiling, roasting, drying, and microwave heating significantly influenced the digestibility of both insect species. Notably, drying emerged as the most effective method, leading to a substantial increase in digestibility. Furthermore, we assessed protein quality using the digestible indispensable amino acid score (DIAAS) and found that the choice of the calculation method significantly influenced the evaluation of protein quality. By including the sum of the anhydrous amino acids, we eliminated the potential overestimation of protein content and obtained a more reliable assessment of protein quality. Our results underscore the importance of culinary treatments and calculation methods in determining the suitability of insects as protein sources for human nutrition.